Processos de inclusão digital: um estudo etnográfico - Bolzan, Larissa Medianeira (2013)
Digital inclusion is a dynamic process that by accessing ICTs makes possible the knowledge appropriation on information technology and communication, so that the individual can develop and refine skills capable of providing autonomy on digital tools and critical use of them. Also it is essential that the digital inclusion process enables the interaction enhancement, i.e., knowledge update (LÖBLER et al., 2011). From the Administration viewpoint, studying the digital inclusion process becomes pertinent while according to Fonseca and Lima (2007), the introduction of new digital and automation technologies led to a break in workers' knowledge, creating a knowledge gap that is responsible for many accidents, according to the authors. In the public administration perspective the importance of exploring this theme is centered on the need for evaluation of public policies towards digital inclusion. Regarding to research in the digital inclusion topic, Notten et al. (2008) and Löbler et al. (2011) studies showed a gap: the digital inclusion process in the individual perception. Therefore, the central research question of this study is: How does happen the digital inclusion process? In order to facilitate the search for this answer, the following specific objectives were built: (i) Describe the individual learning process regarding ICTs, (ii) Identify factors that imply in the digital inclusion process and, (iii) Verify the individual effects of the digital inclusion process. The method used in this study belongs to the interpretive paradigm. It is an ethnography, which is justified because the digital inclusion process, in the dimension of individual knowledge ownership, is a phenomenon that cannot be captured in its essence, by the researcher, through quantitative techniques, the only way to understand it is the observation in its reality (CAVEDON, 2008). Participant observation, semi structured interviews and digital photos were used as data collection technique. As contribution, this dissertation describes how does the knowledge appropriation about ICT, exposes the factors that influence the digital inclusion and the results of this process. Also, it was possible to verify that many behaviors are repeated, such as difficulties, anxiety, facilities, and others. Through observations, I observed social inclusion as a result of the digital inclusion process. In this regard Çilan et al. (2009), Griebler, Rokoski e Dalri (2010) e Ferro et al. (2011) comprehend the digital inclusion of individuals outside the social development process as a tool to whose main target is social inclusion. Hence, the results allow me to judge that digital inclusion projects ethnographed were an effective tool to achieve the goal of including socially the students, now digital and social included.